Correction of Skeletal Discrepancy and Facial Aesthetics by Combination of Orthodontic Management and Orthognathic Surgery - Hasan, Md Nazmul; Alam, Md Badiul; Khan, Mohammad Sayedur Rahman (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Clinical management of non-growing adult patients with dentofacial deformity could be provided with better outcome when approach in-combined with orthodontic and orthognathic surgery than that of single approach alone. This study describes a case of a 26years old Bangladeshi female presented with bimaxillary protrusion treated with the combination of orthodontic and orthognathic surgery. J Bangladesh Coll Phys Surg 2014; 32: 235-240